Method for preparing nitrogen-doped carbon materials with bicontinuous structure based on co-assembly method and its application
The preparation of dual continuous structure nitrogen-doped carbon materials through co-assembly method solved the problem of poor rate performance of sodium/chlorine batteries, and achieved high discharge current density and excellent cycling performance.
Patent Information
- Application Number
- CN202311216749.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-09-20
AI Technical Summary
The current rechargeable sodium/chlorine gas batteries have poor rate performance, mainly because the solid-liquid-gas three-phase interface is not conducive to the rapid transmission of electrons and sodium ions, resulting in poor adsorption and reaction kinetics of Cl2.
A dual continuous structure nitrogen-doped carbon material prepared based on the co-assembly method is used as the positive electrode material, and the material is obtained by calcining treatment, which improves the structure and performance of the solid-liquid-gas three-phase interface.
It significantly improves the maximum discharge current density of sodium/chlorine batteries to reach 16000mA g-1, improves the cycle performance and charging capacity, and has excellent theoretical practical prospects.
Smart Images

Figure CN117430111B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of bicontinuous structure carbon materials, and specifically relates to a method for preparing bicontinuous structure nitrogen-doped carbon materials based on a co-assembly method and applications thereof, and particularly relates to the application of the bicontinuous structure nitrogen-doped carbon materials as materials for preparing sodium / chlorine batteries. Background Art
[0002] Nowadays, technological advances require higher performance and more sustainable rechargeable batteries for the rapidly growing energy storage. Rechargeable sodium-ion batteries are considered a promising alternative to lithium-ion batteries, thanks to the higher abundance of sodium in the earth's crust (almost 1,300 times that of lithium). Over the past decade, the electrochemical performance of sodium-ion batteries has been improved by studying conversion battery reactions, such as sodium-sulfur, sodium-oxygen, and sodium-halide batteries. In recent years, the emerging rechargeable sodium / chlorine (Na / Cl2) battery has shown a 1200 mAh g / m2 charge capacity at a discharge voltage of ~3.5 V based on the reversible NaCl / Cl2 redox reaction, i.e., the NaCl generated during the initial discharge process is oxidized to Cl2 during the charge process and reduced back to NaCl during the subsequent discharge process. -1 Although the battery exhibits excellent performance, its complex solid-liquid-gas (carbon-electrolyte-chlorine) three-phase interface is not conducive to the transport of electrons and sodium ions, resulting in poor rate performance. For example, the maximum discharge current density of the battery is only 150 mA g -1 (1. Zhu, G., Tian, X., Tai, HC, et al. Rechargeable Na / Cl2 and Li / Cl2 batteries[J]. Nature, 2021, 596(7873): 525-530), which seriously hinders the sustainable application of rechargeable sodium / chlorine batteries, especially for grid energy storage that requires high rate capability.
[0003] As the substrate connecting the solid-liquid-gas three-phase interface, carbon materials play a vital role in sodium / chlorine (Na / Cl2) batteries. Traditional carbon cathode materials usually have high porosity and large specific surface area, which are important for the conversion between NaCl and Cl2. However, the discontinuous paths between traditional carbon sphere particles still hinder the transport of fast electrons and sodium ions, thereby reducing the rate performance of the battery. In addition, the chemical composition of carbon materials may significantly regulate the interaction and reaction kinetics of gas products (Cl2) with carbon materials, but for rechargeable sodium / chlorine batteries, this has not been fully studied and has no recognized theoretical basis.
[0004] Based on this, it can be inferred that improving the solid-liquid-gas triple-phase interface may be crucial for rechargeable sodium / chlorine batteries, but at the same time this technology is also highly challenging. The triple-phase interface needs to allow fast electron and sodium ion transport and enhance the adsorption and reaction kinetics of Cl2 to achieve high rate performance. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a method for preparing a bicontinuous structure nitrogen-doped carbon material based on a co-assembly method and its application. The bicontinuous structure nitrogen-doped carbon material is tested as a positive electrode material for a sodium / chlorine battery, and the maximum discharge current density of the battery sample can reach 16000mA g -1 , which is more than two orders of magnitude higher than the existing technical literature. It also has excellent cycle performance and high charging capacity, and has excellent theoretical and practical prospects.
[0006] To achieve the above objectives, the present invention first provides a method for preparing a dual-continuous structure nitrogen-doped carbon material based on a co-assembly method, which is achieved by adopting a technical solution consisting of the following technical measures.
[0007] A method for preparing a bicontinuous structure nitrogen-doped carbon material based on a co-assembly method mainly comprises the following steps:
[0008] (1) 10-30 mg of polystyrene-b-polyethylene oxide (PS 222 -b-PEO 45 ) and 10-30 μL of pyrrole are completely mixed and dissolved in an organic solvent to serve as a precursor solution;
[0009] (2) adding 1.5 to 2.5 mL of a poor solvent to the precursor solution obtained in step (1) at a rate of 0.5 to 2 mL / h, stirring during the addition, and continuing to stir for 1 to 3 hours after the addition is completed; then adding a polymerization initiator to carry out a polymerization reaction, and washing and drying the polymerization reaction product as an intermediate product;
[0010] (3) calcining the intermediate product obtained in step (2) to obtain a bicontinuous structure nitrogen-doped carbon material; wherein the calcination treatment is specifically as follows: heating the intermediate product obtained in step (2) to 350-400°C under an inert gas atmosphere, retaining the heat treatment at this temperature for 2-3 hours, then heating it to 750-850°C, continuing the heat treatment at this temperature for 2-3 hours, and obtaining a bicontinuous structure nitrogen-doped carbon material after cooling.
[0011] In this article, the polystyrene-b-polyethylene oxide (PS 222 -b-PEO 45) is a synthetic preparation product disclosed by the inventor of the present invention in a previously published paper. The specific preparation method can be referred to the following paper:
[0012] 2. Mai, Y., Eisenberg, A. Controlled incorporation of particles into the central portion of vesicle walls [J]. Journal of the American Chemical Society, 2010, 132(29): 10078-10084.
[0013] Typically, the polystyrene-b-polyethylene oxide (PS 222 -b-PEO 45 ), those skilled in the art can refer to the preparation method described in the above-mentioned public literature and use atom transfer radical polymerization to prepare the target product polystyrene-b-polyethylene oxide (PS 222 -b-PEO 45 ).
[0014] In order to better illustrate the present invention and provide a preparation method for reference, the polystyrene-b-polyethylene oxide (PS 222 -b-PEO 45 ), and its specific preparation method is as follows:
[0015] Polystyrene-b-polyethylene oxide (PS 222 -b-PEO 45 ) is synthesized by atom transfer radical polymerization, and the synthesis process is mainly divided into two steps:
[0016] The first step is the macromolecular initiator PEO 45 The specific steps for the synthesis of -Br are as follows: First, weigh 50 g of polyethylene glycol monomethyl ether (PEO 45 -OH) was dissolved in 200mL of dichloromethane, and then 6.2mL of triethylamine was added, and the system was cooled to 0°C to obtain a polymer solution; 6.2mL of 2-bromoisobutyryl bromide was dissolved in 30mL of dichloromethane as a mixed solution, the mixed solution was placed in a constant pressure funnel, and slowly added dropwise to the polymer solution under ice bath conditions, sealed and stirred overnight to obtain a mixed solution; most of the solvent was removed from the mixed solution by vacuum rotary evaporation, 1L of isopropanol was added to the remaining concentrated solution, and the temperature was raised to 80°C to completely dissolve the polymer, and then the system was lowered to 0°C for recrystallization. After recrystallization with isopropanol twice, the mother liquor was filtered, and the obtained white solid was rinsed with ice ether for several times, vacuum dried at room temperature and used as a macromolecular initiator PEO. 45 -Br;
[0017] The second step is polystyrene-b-polyethylene oxide (PS 222 -b-PEO 45 ) synthesis: First, add 1g of macroinitiator PEO into a 200mL Shrek bottle. 45 -Br, 50 mg of cuprous bromide, 80 μL of pentamethyldiethylenetriamine and 12 mL of styrene; freeze-vacuum-thaw with liquid nitrogen for three times to remove oxygen from the Shrek bottle, then stir the mixture at 120°C for about 4 hours under nitrogen protection, and stop passing nitrogen after the sample solidifies; then dissolve the solidified product in tetrahydrofuran, filter out copper salt in alkaline alumina, remove most of the solvent from the resulting solution by vacuum rotary evaporation, then drop it in methanol for precipitation, and the precipitated white solid is polystyrene-b-polyethylene oxide (PS 222 -b-PEO 45 )product.
[0018] In this article, the organic solvent in step (1) should be an organic solvent that can completely mix and dissolve polystyrene-b-polyethylene oxide and pyrrole based on the common knowledge of those skilled in the art. For the dissolution of polystyrene-b-polyethylene oxide, an organic solvent with good solubility for both polystyrene and polyethylene oxide, such as 1,4-dioxane solvent, should be selected according to the common knowledge of block polymers in the art.
[0019] It should be noted that the organic solvent selected in step (1) must be able to completely mix and dissolve polystyrene-b-polyethylene oxide and pyrrole, so that the pyrrole and polyethylene oxide chain segments interact with each other, thereby making the intermediate product obtained in step (2) have a bicontinuous structure. If the solubility of the organic solvent for the solute is insufficient, the intermediate product obtained in step (2) will not have a bicontinuous structure, and may produce adverse factors such as side reaction products and vesicle structures.
[0020] In one of the technical solutions, based on laboratory conditions, the organic solvent in step (1) is a mixture of 1,4-dioxane and N,N-dimethylformamide in a volume ratio of (76-88): (12-24) as an organic solvent to achieve better solubility.
[0021] In one technical solution, under laboratory conditions, when the organic solvent in step (1) is a mixture of 1,4-dioxane and N,N-dimethylformamide in a volume ratio of (76-88): (12-24), 10-30 mg of polystyrene-b-polyethylene oxide (PS 222 -b-PEO 45) and 10-30 μL pyrrole are added to 2-4 mL of organic solvent and stirred at room temperature for 2-4 h to allow the solute to be completely mixed and dissolved.
[0022] Herein, the poor solvent in step (2) is a conventional poor solvent selected based on the self-assembly behavior of polymers in the co-assembly method in the art, for example, deionized water is conventionally used as the poor solvent.
[0023] It should be noted that, through actual experiments, the dropwise addition rate and the total amount of the poor solvent in step (2) will significantly affect the generation of the bicontinuous structure of the intermediate product obtained in step (2), especially if the dropwise addition rate is too fast and the total amount of the dropwise addition is too low, the intermediate product will not have a bicontinuous structure, and may produce side reaction products and produce unfavorable factors such as vesicle structure and layered structure. Based on the above experimental facts, the present invention limits the dropwise addition rate and the total amount of the poor solvent in step (2).
[0024] In one preferred technical solution, in step (2), 1.5 to 2.5 mL of a poor solvent is preferably added dropwise at a rate of 0.8 to 1 mL / h, and the poor solvent is deionized water.
[0025] Herein, the polymerization initiator in step (2) is a conventional polymerization initiator capable of initiating pyrrole polymerization reaction. Those skilled in the art can make a specific selection based on the common knowledge of conventional polymerization reaction and the polymerization initiators suitable for pyrrole polymerization reaction recorded in existing literature.
[0026] In one of the technical solutions, the polymerization initiator selected in step (2) includes any one of ammonium persulfate and ferric chloride.
[0027] In order to better illustrate the present invention and provide a technical solution for reference, the step (2) of adding a polymerization initiator to carry out a polymerization reaction is specifically as follows: adding 0.5 to 2 mL of an aqueous solution of ammonium persulfate (mass concentration of 80 mg / mL) and carrying out a polymerization reaction with stirring for 7 to 9 hours.
[0028] In one of the more preferred technical solutions, in order to make the intermediate product obtained in step (2) have a better morphology and improve its purity, it is preferred to adjust the pH value to 9 to 11 during the polymerization reaction in step (2) to reduce the polymerization reaction rate. The pH value is adjusted by conventionally adding alkali (such as sodium hydroxide).
[0029] In one of the technical solutions, the calcination treatment in step (3) has a heating rate of 2 to 3°C / min.
[0030] In this article, the mixing, washing and drying all follow the conventional principles in chemical processes, and those skilled in the art can perform specific operations according to common knowledge.
[0031] In one technical solution, under laboratory conditions, the washing in step (2) is preferably centrifugal washing using ethanol, water and tetrahydrofuran in sequence.
[0032] On the other hand, the present invention also provides the use of the bicontinuous structure nitrogen-doped carbon material prepared by the co-assembly method as a battery material, especially a sodium / chlorine battery material.
[0033] In one of the technical solutions, the bicontinuous structure nitrogen-doped carbon material is used to prepare the positive electrode of a sodium / chlorine battery.
[0034] The present invention has the following beneficial effects:
[0035] 1. Compared with the positive electrode carbon materials used in the prior art, the double continuous structure nitrogen-doped carbon material provided by the present invention has a charge transfer resistance (R ct ) is significantly reduced, indicating that the charge transfer at the interface with the electrolyte is significantly improved.
[0036] 2. Compared with the positive electrode carbon material used in the prior art, the bicontinuous structure nitrogen-doped carbon material provided by the present invention has a significantly enhanced ion diffusion coefficient, which proves that sodium ions can diffuse rapidly in the bicontinuous structure nitrogen-doped carbon material, which is significantly beneficial to enhancing the rate performance of the sodium / chlorine battery.
[0037] 3. The bicontinuous structure nitrogen-doped carbon material provided by the present invention has been tested to have a maximum discharge current density of 16000 mA g when used as a positive electrode material. -1 , which is more than two orders of magnitude higher than the existing technical literature.
[0038] 4. The bicontinuous structure nitrogen-doped carbon material provided by the present invention has been tested to be effective as a positive electrode material at a higher charge depth (800 mAh g -1 ) and exhibited excellent cycling performance for more than 200 cycles.
[0039] 5. The bicontinuous structure nitrogen-doped carbon material provided by the present invention has been tested as a positive electrode material and has a high capacity of 2000 mAh g -1 It shows a high Coulombic efficiency of over 99% at a high charge capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1The application principle diagram, bicontinuous structure schematic diagram, principle schematic diagram, electron microscope photo, element spectrum diagram and X-ray diffraction diagram of the bicontinuous structure nitrogen-doped carbon material prepared in Example 1 of the present invention. In the figure, (a) Na / Cl2 battery schematic diagram; (b) three-dimensional structure schematic diagram of the bicontinuous structure; (c) principle schematic diagram of the efficient transmission of sodium ions and electrons at the solid-liquid-gas three-phase interface (i.e., carbon-electrolyte-chlorine three-phase interface); (d) electron scanning microscope image of the bicontinuous structure nitrogen-doped carbon material prepared in Example 1, and the inset is a local magnified view of the structure; (e) transmission electron microscope image of the bicontinuous structure nitrogen-doped carbon material prepared in Example 1, and the inset is a local magnified view of the structure; (f) high-angle annular dark field scanning transmission electron microscope image and energy dispersion element spectrum diagram of the bicontinuous structure nitrogen-doped carbon material prepared in Example 1; (g) low-angle X-ray diffraction pattern of the bicontinuous structure nitrogen-doped carbon material prepared in Example 1, which shows five characteristic peaks corresponding to the symmetry The
[100] ,
[110] ,
[111] ,
[200] and
[210] crystal planes.
[0041] Figure 2 The electrochemical performance diagrams of the Na / Cl2 battery assembled with the products obtained in Example 1 and Comparative Examples 1-2 as samples. In the figure, (a) when Bi-NC, NC and bareC are used as positive electrodes, the Na / Cl2 battery at 2000mA g -1 (a) The constant current discharge curves under the current density; (b) When Bi-NC, NC and bareC are used as positive electrodes, the Na / Cl2 battery has a current density and specific capacity of 2000 mA g -1 and 500mAh g -1 (c) Rate performance of Na / Cl2 battery with Bi-NC, NC and Bare C as positive electrode; (d) Rate performance of Na / Cl2 battery with Bi-NC as positive electrode at charge and discharge rates of 250-16000 mA g -1 (e) When Bi-NC, NC and Bare C are used as positive electrodes, the Na / Cl2 battery has a current density of 2000 mA g -1 , capacity is 500mAh g -1 (f) Comparison of the discharge performance of Na / Cl2 batteries with Bi-NC as the positive electrode and reported sodium-based batteries; (g) Impedance diagrams with Bi-NC, NC and bare C as the positive electrode, the inset shows the impedance diagram with Bi-NC as the positive electrode;
[0042] Figure 3The products prepared in Example 1 and Comparative Example 1 are used as samples to assemble the discharge product distribution diagram and ion transport mechanism analysis diagram of Na / Cl2 batteries. In the figure, the distribution of secondary ion fragments of NaCl and C in (a) Bi-NC and (b) NC positive electrodes in three-dimensional cross-sections constructed based on sputtering and time-of-flight secondary ion mass spectrometry; (c) three-dimensional distribution of secondary ion fragments of NaCl and C in Bi-NC and (d) NC positive electrodes; (e) depth distribution curve of NaCl secondary ion fragments after complete discharge of Bi-NC and NC positive electrodes; (f) schematic diagram of Bi-NC positive electrode model, which consists of approximately 400 Bi-NC particles; (g) schematic diagram of NC positive electrode model, which consists of approximately 373k NC particles. The unit of the cube in the model is 10 3 μm 3 The particle size and pore structure of Bi-NC and NC in the simulated model based on the results of SEM. (h) The distribution of NaCl along the Z-axis obtained from the theoretical simulation results.
[0043] Figure 4 The diagram is a mechanism analysis diagram of Cl2 adsorption by the bicontinuous nitrogen-doped carbon material prepared in Example 1 of the present invention and a kinetic analysis diagram of the NaCl / Cl2 conversion reaction. In the figure, (a) high-resolution N1s photoelectron energy spectrum before and after Bi-NC charging; (b) charge density analysis of different Cl2 adsorption sites on Bi-NC, green balls and blue balls represent C and N elements, respectively, and red and blue areas represent positive and negative charge areas, respectively; (c, d) simulated optimized geometric structures and corresponding Cl2 adsorption energies on graphene, graphite N, pyrrole N and pyridinic N; (e) changes in the adsorption of intermediate products by pyrrole N during charging and discharging; (f) changes in relative free energy during the charging process of graphene, graphite N, pyrrole N and pyridinic N.
[0044] Figure 5 The schematic diagram of the fast NaCl / Cl2 redox mechanism of the Na / Cl2 battery assembled with the product prepared in Example 1 as a sample. In the figure, (a) the conventional nanocarbon particles lead to NaCl aggregation and weak Cl2 adsorption; (b) Bi-NC with dual continuous electron and ion transfer paths achieves uniform deposition of NaCl and effective Cl2 adsorption, thereby promoting the fast redox process of NaCl / Cl2. DETAILED DESCRIPTION
[0045] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Although it is believed that those of ordinary skill in the art fully understand the following terms, the following definitions are still stated to help illustrate the subject matter disclosed by the present invention.
[0046] A method for preparing a bicontinuous structure nitrogen-doped carbon material based on a co-assembly method mainly comprises the following steps:
[0047] (1) 10-30 mg of polystyrene-b-polyethylene oxide (PS 222 -b-PEO 45 ) and 10-30 μL of pyrrole are completely mixed and dissolved in an organic solvent to serve as a precursor solution;
[0048] (2) adding 1.5 to 2.5 mL of a poor solvent to the precursor solution obtained in step (1) at a rate of 0.5 to 2 mL / h, stirring during the addition, and continuing to stir for 1 to 3 hours after the addition is completed; then adding a polymerization initiator to carry out a polymerization reaction, and washing and drying the polymerization reaction product as an intermediate product;
[0049] (3) calcining the intermediate product obtained in step (2) to obtain a bicontinuous structure nitrogen-doped carbon material; wherein the calcination treatment is specifically as follows: heating the intermediate product obtained in step (2) to 350-400°C under an inert gas atmosphere, retaining the heat treatment at this temperature for 2-3 hours, then heating it to 750-850°C, continuing the heat treatment at this temperature for 2-3 hours, and obtaining a bicontinuous structure nitrogen-doped carbon material after cooling.
[0050] In this article, the polystyrene-b-polyethylene oxide (PS 222 -b-PEO 45 ) is a synthetic preparation product disclosed by the inventor of the present invention in a previously published paper. The specific preparation method can be referred to the following paper:
[0051] 2.Mai.Y,Eisenberg.A.Controlled incorporation of particles into the central portion of vesicle walls[J].Journal of the American Chemical Society, 2010,132(29):10078-10084.
[0052] Typically, the polystyrene-b-polyethylene oxide (PS 222 -b-PEO 45 ), those skilled in the art can refer to the preparation method described in the above-mentioned public literature and use atom transfer radical polymerization to prepare the target product polystyrene-b-polyethylene oxide (PS 222 -b-PEO 45 ).
[0053] In order to better illustrate the present invention and provide an embodiment for reference, the polystyrene-b-polyethylene oxide (PS 222 -b-PEO 45 ), and its specific preparation method is as follows:
[0054] Polystyrene-b-polyethylene oxide (PS 222 -b-PEO 45 ) is synthesized by atom transfer radical polymerization, and the synthesis process is mainly divided into two steps:
[0055] The first step is the macromolecular initiator PEO 45 The specific steps for the synthesis of -Br are as follows: First, weigh 50 g of polyethylene glycol monomethyl ether (PEO 45 -OH) was dissolved in 200mL of dichloromethane, and then 6.2mL of triethylamine was added, and the system was cooled to 0°C to obtain a polymer solution; 6.2mL of 2-bromoisobutyryl bromide was dissolved in 30mL of dichloromethane as a mixed solution, the mixed solution was placed in a constant pressure funnel, and slowly added dropwise to the polymer solution under ice bath conditions, sealed and stirred overnight to obtain a mixed solution; most of the solvent was removed from the mixed solution by vacuum rotary evaporation, 1L of isopropanol was added to the remaining concentrated solution, and the temperature was raised to 80°C to completely dissolve the polymer, and then the system was lowered to 0°C for recrystallization. After recrystallization with isopropanol twice, the mother liquor was filtered, and the obtained white solid was rinsed with ice ether for several times, vacuum dried at room temperature and used as a macromolecular initiator PEO. 45 -Br;
[0056] The second step is polystyrene-b-polyethylene oxide (PS 222 -b-PEO45 ) synthesis: First, add 1g of macroinitiator PEO into a 200mL Shrek bottle. 45 -Br, 50 mg of cuprous bromide, 80 μL of pentamethyldiethylenetriamine and 12 mL of styrene; freeze-vacuum-thaw with liquid nitrogen for three times to remove oxygen from the Shrek bottle, then stir the mixture at 120°C for about 4 hours under nitrogen protection, and stop passing nitrogen after the sample solidifies; then dissolve the solidified product in tetrahydrofuran, filter out copper salt in alkaline alumina, remove most of the solvent from the resulting solution by vacuum rotary evaporation, then drop it in methanol for precipitation, and the precipitated white solid is polystyrene-b-polyethylene oxide (PS 222 -b-PEO 45 )product.
[0057] In this article, the organic solvent in step (1) should be selected based on the common knowledge of those skilled in the art to be an organic solvent that can completely mix and dissolve polystyrene-b-polyethylene oxide and pyrrole, wherein the dissolution of polystyrene-b-polyethylene oxide should be selected according to the common knowledge of block polymers in the art to select an organic solvent that has good solubility for both polystyrene and polyethylene oxide. In one embodiment, the organic solvent is selected as a 1,4-dioxane solvent.
[0058] It should be noted that the organic solvent selected in step (1) must be able to completely mix and dissolve polystyrene-b-polyethylene oxide and pyrrole, so that the pyrrole and polyethylene oxide chain segments interact with each other, thereby making the intermediate product obtained in step (2) have a bicontinuous structure. If the solubility of the organic solvent for the solute is insufficient, the intermediate product obtained in step (2) will not have a bicontinuous structure, and may produce adverse factors such as side reaction products and vesicle structures.
[0059] In one embodiment, based on laboratory conditions, the organic solvent in step (1) is a mixture of 1,4-dioxane and N,N-dimethylformamide in a volume ratio of (76-88): (12-24) as an organic solvent to achieve better solubility.
[0060] In one embodiment, under laboratory conditions, when the organic solvent in step (1) is prepared by mixing 1,4-dioxane and N,N-dimethylformamide in a volume ratio of (76-88): (12-24), 10-30 mg of polystyrene-b-polyethylene oxide (PS 222 -b-PEO 45 ) and 10-30 μL pyrrole are added to 2-4 mL of organic solvent and stirred at room temperature for 2-4 h to allow the solute to be completely mixed and dissolved.
[0061] In one embodiment, the polystyrene-b-polyethylene oxide in step (1) is 10 to 30 mg, for example, 10 mg, 11 mg, 12 mg, 13 mg, 14 mg, 15 mg, 16 mg, 17 mg, 18 mg, 19 mg, 20 mg, 21 mg, 22 mg, 23 mg, 24 mg, 25 mg, 26 mg, 27 mg, 28 mg, 29 mg, 30 mg Or any range or point value therebetween; the pyrrole is 10-30 μL, for example, 10 μL, 11 μL, 12 μL, 13 μL, 14 μL, 15 μL, 16 μL, 17 μL, 18 μL, 19 μL, 20 μL, 21 μL, 22 μL, 23 μL, 24 μL, 25 μL, 26 μL, 27 μL, 28 μL, 29 μL, 30 μL or any range or point value therebetween.
[0062] It is noted that the proportional increase or decrease in the amount of polystyrene-b-polyethylene oxide and pyrrole added in step (1) should also be considered as the scope of protection of this patent.
[0063] Herein, the poor solvent in step (2) is a conventional poor solvent selected based on the self-assembly behavior of polymers in the co-assembly method in the art. In one embodiment, deionized water is used as the poor solvent.
[0064] It should be noted that, through actual experiments, the dropwise addition rate and the total amount of the poor solvent in step (2) will significantly affect the generation of the bicontinuous structure of the intermediate product obtained in step (2), especially if the dropwise addition rate is too fast and the total amount of the dropwise addition is too low, the intermediate product will not have a bicontinuous structure, and may produce side reaction products and produce unfavorable factors such as vesicle structure and layered structure. Based on the above experimental facts, the present invention limits the dropwise addition rate and the total amount of the poor solvent in step (2).
[0065] In one embodiment, in step (2), the poor solvent is added dropwise at a rate of 0.5 to 2 mL / h, for example, a rate of 0.5 mL / h, 0.6 mL / h, 0.7 mL / h, 0.8 mL / h, 0.9 mL / h, 1.0 mL / h, 1.1 mL / h, 1.2 mL / h, 1.3 mL / h, 1.4 mL / h, 1.5 mL / h, 1.6 mL / h, 1.7 mL / h, 1.8 mL / h, 1.9 mL / h, 2.0 mL / h or any range or point value therebetween; 1.5 to 2.5 mL of the poor solvent is added dropwise, for example, 1.5 mL, 1.6 mL, 1.7 mL, 1.8 mL, 1.9 mL, 2.0 mL, 2.1 mL, 2.2 mL, 2.3 mL, 2.4 mL, 2.5 mL or any range or point value therebetween.
[0066] In one preferred embodiment, in step (2), 1.5 to 2.5 mL of a poor solvent is preferably added dropwise at a rate of 0.8 to 1 mL / h, and the poor solvent is deionized water.
[0067] It should be noted that the poor solvent droplet acceleration rate and the total amount of droplet addition in step (1) increase or decrease in proportion to the precursor solution, and should also be considered as the scope of protection of this patent.
[0068] Herein, the polymerization initiator in step (2) is a conventional polymerization initiator capable of initiating pyrrole polymerization reaction. Those skilled in the art can make a specific selection based on the common knowledge of conventional polymerization reaction and the polymerization initiators suitable for pyrrole polymerization reaction recorded in existing literature.
[0069] In one embodiment, the polymerization initiator in step (2) is selected from any one of ammonium persulfate and ferric chloride.
[0070] In one embodiment, after the dropwise addition in step (2), stirring is continued for 1 to 3 hours, for example, 1 hour, 2 hours, 3 hours or any range or point value therebetween.
[0071] In order to better illustrate the present invention and provide an implementation method for reference, the step (2) of adding a polymerization initiator to carry out a polymerization reaction is specifically: adding 0.5 to 2 mL of an aqueous solution of ammonium persulfate (mass concentration of 80 mg / mL) and carrying out the polymerization reaction with stirring for 7 to 9 hours.
[0072] In one of the more preferred embodiments, in order to make the intermediate product obtained in step (2) have a better morphology and improve its purity, it is preferred that during the polymerization reaction in step (2), the pH value is adjusted to 9-11 (for example, the pH value is 9, 10, 11 or any range or point value therebetween) to reduce the polymerization reaction rate. The pH value is adjusted by conventionally adding a base (for example, sodium hydroxide).
[0073] In one embodiment, the calcination treatment in step (3) is to heat the intermediate product obtained in step (2) to 350-400°C, for example, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C or any range or point value therebetween under an inert gas atmosphere; and then heat it to 750-850°C, for example, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C or any range or point value therebetween.
[0074] In one embodiment, the calcination treatment in step (3) has a heating rate of 2 to 3°C / min.
[0075] In this article, the mixing, washing and drying all follow the conventional principles in chemical processes, and those skilled in the art can perform specific operations according to common knowledge.
[0076] In one technical solution, under laboratory conditions, the washing in step (2) is preferably centrifugal washing using ethanol, water and tetrahydrofuran in sequence.
[0077] On the other hand, the present invention also provides the use of the bicontinuous structure nitrogen-doped carbon material prepared by the co-assembly method as a battery material, especially a sodium / chlorine battery material.
[0078] In one of the technical solutions, the bicontinuous structure nitrogen-doped carbon material is used to prepare the positive electrode of a sodium / chlorine battery.
[0079] The present invention will be further explained in detail with reference to the following examples. However, it should be understood by those skilled in the art that these examples are provided for illustrative purposes only and are not intended to limit the present invention.
[0080] Example
[0081] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. The specific conditions not specified in the examples are carried out according to the conditions recommended by normal conditions or manufacturers. The reagents used or the instruments not specified by the manufacturer are all conventional products that can be obtained commercially. The application should not be construed as being limited to the specific examples described.
[0082] 1. Raw materials
[0083] Polyethylene glycol monomethyl ether (PEO 45 -OH, 45 indicates the degree of polymerization), cuprous bromide, styrene, 2-bromoisobutyryl bromide and triblock copolymer F-127 (PEO 106 -PPO 70 -PEO 106 ,M w :12,600) was purchased from Aldrich.
[0084] Triethylamine (Et3N), N,N,N',N',N"-pentamethyldiethylenetriamine (PMDETA), tetrahydrofuran (THF), N,N-dimethylformamide (DMF), 1,4-dioxane, ammonium persulfate ((NH4)2S2O8, APS), pyrrole (Py), sodium hydroxide (NaOH), aqueous ammonia solution (NH4OH, 25 wt%), resorcinol and aqueous formaldehyde solution (36-38 wt%) were purchased from Adamas Reagent (Shanghai). Deionized water was used in all experiments. Unless otherwise stated, all reagents were of analytical reagent (AR) grade and used without further purification.
[0085] 2. Test Method
[0086] Scanning Electron Microscope (SEM): Observations were performed on a JEOL JSM-7401F field emission scanning electron microscope. A low accelerating voltage (5 kV, point resolution of ~1.4 nm) was used. Each SEM sample was prepared by dropping a liquid containing the sample dispersed in ethanol onto a silicon wafer and then air-drying at room temperature for 24 hours. Before dropping the sample, the silicon wafer was cleaned with 100 mL 80% H2SO4, 35 mL H2O2, and 20 mL ultrapure water at room temperature. The silicon surface was then purged and dried with compressed nitrogen.
[0087] Transmission electron microscopy (TEM): Conventional TEM analysis was performed using a JEOL JEM-2100 microscope equipped with an operating voltage of 200 kV (Cs 1.0 mm, point resolution ) with a LaB6 gun. Images were recorded using a TENGRA CCD camera (2304 × 2304 pixels, fiber aspect ratio 2:1, effective pixel size 18 μm). TEM samples were prepared by dropping a dispersion of the sample in ethanol onto a copper grid and then air-dried at room temperature for 24 h.
[0088] Scanning transmission electron microscopy (STEM): STEM and EDS spectra were performed on a FEI TALOS F200X instrument with an operating voltage of 200 kV. Each STEM sample was prepared by dropping a dispersion of the sample in ethanol on a copper grid and then air-dried at room temperature for 24 hours. The EDS spectrum results were processed using VELOX software.
[0089] Small angle X-ray scattering (SAXS): SAXS curves were provided by the Shanghai Synchrotron Radiation Source, using the third generation synchrotron radiation source and synchrotron radiation recording at the BL10U1 beamline. At room temperature (25°C), the analysis was performed using X-rays with a wavelength of λ = 0.124nm. The SAXS detector is an Eiger 4M, with 2070 and 2167 pixels in both directions, and a pixel size of 75μm. The distance between the sample and the detector can be adjusted to 27.6m. The typical exposure time ranges from 0.1 to 100 seconds.
[0090] Nitrogen adsorption-desorption analysis: Nitrogen adsorption isotherms were measured at 77 K using an Autosorb-iQA3200-4 adsorption analyzer (Quantatech Co., USA). Before measurement, 50 mg of sample was degassed at 150 °C under vacuum for at least 6 hours. The specific surface area was calculated using adsorption data in the relative pressure range of 0.05 to 0.3 using the Brunauer-Emmet-Teller (BET) method. The pore size distribution and pore volume were obtained from the adsorption curve of the isotherm using the Barrett-Joyner-Halenda (BJH) method.
[0091] Powder X-ray diffraction (XRD) pattern: X-ray diffractometer D / MAX-2200 / PC at 6°min -1 The XRD patterns were recorded in the range of 5-80° (2θ) at a rate of 1.5 %. Low-angle XRD patterns were recorded on a SmartLab 9KW (Rigaku, Japan) spectrometer.
[0092] Raman spectroscopy: Raman spectroscopy was performed on an Invia / Reflrx laser micro-Raman spectrometer (Renishaw, 70 England) excited by a 532 nm laser beam.
[0093] X-ray photoelectron spectroscopy (XPS): X-ray photoelectron spectroscopy (XPS) was performed on an AXIS Ultra DLD system (Kratos Co., Japan) using Al Kα radiation as the X-ray source. A small amount of powder sample was pressed on an insulating glue to prepare the XPS sample. The test area size was 300 × 700 μm 2 All samples were dried in vacuum at 70 °C for 1 day before testing. All binding energies were corrected with reference to the C1s binding energy (284.8 eV).
[0094] Gel permeation chromatography (GPC): GPC analysis was performed using a Shimadzu imaging system (GPC, LC-20A, Shimadzu, Japan) with a combination of two columns (Shodex, KF-802 and 804, 300 × 8 mm) and a RID-10A differential refractive index detector. Tetrahydrofuran was used as the eluent at a flow rate of 1 mL min-1 , temperature was 40°C, sample concentration was 2 mg mL -1 The injection volume was 50 μL. A polystyrene standard with a narrow molecular weight distribution was used as a calibration agent (calibration range: 300-67500 g mol -1 ).
[0095] Time-of-flight secondary ion mass spectrometry (TOF-SIMS): Using ION-TOFTOF-SIMS 5, the analysis chamber pressure is less than 1.1×10 -9 mbar. Using pulse 30keV Bi 3+ (0.48pA pulse current) ion beam time-delay extraction organic imaging technology, with 1keV Cs + Ion beam sputtering (69.27~82.74nA current) and 300×300μm 2 Depth profiling of sputtered gratings with an analysis area of 100 × 100 μm 2 .
[0096] Electrochemical measurements: Unless otherwise stated, all electrochemical measurements were performed at 25 °C in a thermostatic test chamber (Neware MHW-200). The charge and discharge performance of the battery was tested using a Neware battery test system (CT-4008Tn-5V50mA-164-U and (CT-4008Tn-5V6A-S1). Electrochemical impedance spectroscopy was measured using a CHI660E electrochemical workstation. Three-electrode electrochemical impedance tests were performed in CR2032 coin cells, with Na metal foil as the counter electrode and reference electrode, and carbon material as the working electrode. The frequency range was 0.01 to 10 Hz, and the perturbation was 5 mV.
[0097] Particle stacking theory calculation: Particle stacking simulation was performed using MATLAB (MathWorks, USA). For the theoretical model, the sizes of the Bi-NC cube model (particle size 0.5-2 μm, framework diameter and pore diameter 33-40 nm) and the NC nanoparticle model (particle size 103-276 nm) were referenced to the electron microscopy results of Bi-NC and NC, respectively. We constructed a 10×10×10 μm 3 The electrode is simulated by a cubic box with random stacking of Bi-NC particles and NC nanoparticles, with volume fractions of 0.53 and 0.56, respectively. The NC nanoparticles form aggregates of about 0.5 μm on the surface, which is also referred to the electron microscopy results. It is assumed that NaCl is uniformly distributed in the pores, so the distribution of NaCl along the depth direction is determined by the pore fraction.
[0098] DFT calculations: Density functional theory (DFT) calculations were performed using the Gaussian 16 package. All DFT calculations were performed using the D3GJ dispersion-corrected B3LYP density functional method. The 6-311+G(D,P) basis set was used. The boundary carbons and attached hydrogens were kept fixed during carbon basis optimization.
[0099] The adsorption energy between chlorine and carbon materials (ΔE ads ) is calculated as follows:
[0100] ΔE ads =E complex -(E chlorine +E substrate )
[0101] ΔE ads represents the adsorption energy of chlorine on carbon materials;
[0102] E complex represents the total energy of chlorine adsorbed on the carbon material substrate;
[0103] E chlorine Represents the energy of a single chlorine gas;
[0104] E substrate Represents the energy of the carbon material substrate.
[0105] An independent gradient model based on Hirshfeld partitioning was established using Multiwfn software to characterize the interaction between chlorine and carbon materials and visualized using VMD software. The electrostatic potentials involved in the analysis were evaluated using the Multiwfn algorithm.
[0106] NaCl to Na on carbon material base + The relative free energy of the transformation with Cl2 is calculated according to the following reaction sequence:
[0107]
[0108] The reaction energies corresponding to the three steps are calculated by the equations:
[0109]
[0110]
[0111]
[0112] represents the total energy of two NaCl molecules adsorbed on the carbon substrate;
[0113] E NaCl Represents the energy of a single NaCl; E substraterepresents the energy of the carbon substrate;
[0114] Represents NaCl2 * The total energy of the intermediate adsorbed on the carbon substrate;
[0115] represents the energy of a single sodium ion; Represents the total energy of a chlorine molecule adsorbed on the carbon substrate.
[0116] Example 1
[0117] This embodiment provides a method for preparing a bicontinuous structure nitrogen-doped carbon material based on a co-assembly method, which mainly includes the following steps:
[0118] (1) 20 mg of polystyrene-b-polyethylene oxide (PS 222 -b-PEO 45 ) and 20 μL of pyrrole were added to 2 mL of organic solvent and stirred at room temperature for 4 h to allow the solutes to be completely mixed and dissolved as a precursor solution;
[0119] The organic solvent is prepared by mixing 1,4-dioxane and N,N-dimethylformamide in a volume ratio of 88:12;
[0120] (2) 2 mL of deionized water was added dropwise to the precursor solution obtained in step (1) at a rate of 1 mL / h, with stirring during the addition process, and stirring was continued for 1 h after the addition was completed; then 1 mL of ammonium persulfate aqueous solution (mass concentration of 80 mg / mL) was added to carry out polymerization reaction with stirring. After the polymerization reaction lasted for 40 min, 100 μL of NaOH aqueous solution (1 mol L -1 ) reducing the polymerization rate, continuing the polymerization reaction until 7 hours, and washing and drying the polymerization product as an intermediate product;
[0121] (3) The intermediate product obtained in step (2) is calcined to obtain a bicontinuous structure nitrogen-doped carbon material; wherein the calcination treatment is specifically as follows: the intermediate product obtained in step (2) is heated to 350°C under argon atmosphere, and heat treated at this temperature for 2 hours, then heated to 800°C, and heat treated at this temperature for 2 hours, and after cooling, a bicontinuous structure nitrogen-doped carbon material is obtained, which is marked as Bi-NC.
[0122] Comparative Example 1
[0123] This comparative example is a method for preparing a nitrogen-doped carbon material without a bicontinuous structure, which mainly includes the following steps:
[0124] (1) 30 mg of triblock copolymer F-127 (Pluronic F127) and 100 μL of pyrrole were added to a mixed solvent of 10 mL of deionized water and 4 mL of ethanol, and stirred at room temperature for 1 h to allow the solutes to be completely mixed and dissolved, thereby obtaining a precursor solution;
[0125] (2) adding 1 mL of an aqueous solution of ammonium persulfate (mass concentration of 80 mg / mL) to the precursor solution obtained in step (1) to carry out a polymerization reaction while stirring. The polymerization reaction was carried out for 12 hours. The polymerization product was washed and dried to obtain an intermediate product.
[0126] (3) calcining the intermediate product obtained in step (2) to obtain a nitrogen-doped carbon material; wherein the calcination treatment is specifically as follows: heating the intermediate product obtained in step (2) to 350°C under an argon atmosphere, retaining the heat treatment at this temperature for 2 hours, then heating it to 800°C, continuing the heat treatment at this temperature for 2 hours, and obtaining a nitrogen-doped carbon material after cooling, which is marked as NC.
[0127] Comparative Example 2
[0128] This comparative example is a method for preparing ordinary carbon materials based on traditional processes, which mainly includes the following steps:
[0129] (1) 0.1 mL of ammonia solution (25 wt%), 8 mL of methanol and 20 mL of deionized water were mixed and stirred for 1 hour, and then 140 μL of formaldehyde solution and 0.1 g of resorcinol were added, and the mixture was stirred at 30° C. for 24 hours. The reaction solution was then transferred to a polytetrafluoroethylene autoclave and statically heated at 100° C. for 24 hours; then the solid product was recovered by centrifugation, and the product was dried as an intermediate product;
[0130] (2) The intermediate product obtained in step (1) is calcined to obtain an ordinary carbon material; wherein the calcination treatment is specifically as follows: the intermediate product obtained in step (2) is heated to 350°C under an argon atmosphere, and heat-treated at this temperature for 2 hours, and then heated to 800°C, and heat-treated at this temperature for 2 hours, and then cooled to obtain an ordinary carbon material, which is marked as bare C.
[0131] In order to facilitate electrochemical testing, the products prepared in Example 1 and Comparative Examples 1 to 2 (Bi-NC, NC and bare C) are used as samples and assembled into half-cells. The specific method is as follows:
[0132] Preparation of electrolyte: prepared in an argon glove box, water and oxygen content less than 1ppm. Thionyl chloride (SOCl2, 99%, Aladdin) and aluminum chloride (AlCl3, 99%, anhydrous, Aladdin) were used without further purification. Sodium bis(trifluoromethylsulfonyl)imide (NaFSI) and bis(trifluoromethylsulfonyl)imide (NaTFSI, 99.9%) were dried in a vacuum oven at 100°C overnight before use.
[0133] 4M AlCl3 was added to SOCl2, and then 2wt% NaFSI and NaTFSI (accounting for 2wt% of the total weight of AlCl3 and SOCl2) were added until they were completely dissolved to obtain an electrolyte.
[0134] Preparation of the positive electrode: The carbon material (Bi-NC, NC or bare C) prepared in Example 1 and Comparative Examples 1 to 2 and a polytetrafluoroethylene binder (60% aqueous dispersion) were mixed in ethanol at a mass ratio of 90:10, and ultrasonically treated until the carbon material was uniformly dispersed in the ethanol to prepare a carbon slurry.
[0135] A manual disc cutter (MTI, MSK-T-10) was used to obtain a 14 mm (1.54 cm) diameter 2 ) and then ultrasonically cleaned it in ethanol for 30 minutes to remove surface impurities.
[0136] The prepared carbon slurry (60 μL each time) was dropped onto a nickel foam disc on a hot plate at 80 °C to allow the ethanol to evaporate completely; this process was repeated until the desired carbon mass loading was 2.5 mg cm -2 , and then placed in a vacuum oven at 80°C for drying overnight, and then further pressed to obtain the positive electrode.
[0137] Preparation of Na / Cl2 cells: The cells were prepared in an argon glove box with water and oxygen content below 1 ppm. The Na anode was prepared by cutting off the surface oxide layer of the Na cube with a blade and then pressing it into a disc. Two layers of glass fiber filter paper (GF / D, Whatman) were used as separators. 150 μL of electrolyte was used for each cell. CR2023 and SS316 button cell cases were used for battery assembly, and a digital voltage-controlled voltage clamp (MTI, 105MSK-160E) was used to encapsulate the cells. Silicone was applied to the edges of the coin cell to seal the case as an additional layer of protection to prevent water and air from leaking into the cell.
[0138] 3. Test conclusion
[0139] like Figure 1As shown in the figure, a Na / Cl2 battery was constructed based on a bicontinuous structure (bicontinuous carbon) as the positive electrode material. The average diameter of the bicontinuous structure is 2.3 microns, showing an ordered and continuous mesoporous structure, with average pore and framework diameters of 39nm and 34nm respectively, and its framework contains heteroatom N element doping. This bicontinuous structure with a three-dimensional continuous pore structure and framework can achieve rapid sodium ion and electron transport, effectively improving the slow reaction kinetics caused by discontinuous ion-electron transport in traditional carbon materials.
[0140] like Figure 2 As shown in Figure 2, the bicontinuous structure (bicontinuous carbon) exhibits excellent performance as a positive electrode material in Na / Cl2 batteries. Figure 2 As shown in (a) to (b), compared with NC without bicontinuous structure and bare C without bicontinuous structure and N doping, the bicontinuous structure shows the highest single discharge capacity and the smallest electrochemical polarization, which is because the bicontinuous structure can achieve fast ion and electron transport. In terms of rate performance, the bicontinuous structure can even achieve high rate performance of 16,000mA g -1 480mAh g -1 reversible cycle, far exceeding the rate performance that NC and bare C can achieve (such as Figure 2 (c) to (d)). The electrochemical impedance spectroscopy also proves that the bicontinuous structure has a smaller charge transfer resistance, further proving the excellent electron transport on the positive electrode material ( Figure 2 (g)). Compared with other sodium-based conversion batteries, the Na / Cl2 battery with a bicontinuous structure as the positive electrode shows obvious performance advantages ( Figure 2 (f)). At a current density of 2,000 mA g -1 And the specific capacity is 500mAh g -1 Under the condition of 2 The battery can be cycled stably for 250 cycles ( Figure 2 (e)).
[0141] Figure 2 The reported sodium-based battery literature marked in (f) is as follows:
[0142] 3. Xu,
[0143] 4.Ye,C.,Jin,H.,Shan,J.,et al.A Mo5N6 electrocatalyst for efficientNa2S electrodeposition in room-temperature sodium-sulfur batteries[J].NatureCommunications,2021,12(1):7195;
[0144] 5.Xiang,L.,Yuan,S.,Wang,F.,et al.Porous polymer cubosomes withordered single primitive bicontinuous architecture and their sodium-iodinebatteries[J].Journal of the American Chemical Society,2022,144(34):15497-15508.;
[0145] 6.Gong,D.,Wang,B.,Zhu,J.,et al.An iodine quantum dots basedrechargeable sodium-iodine battery[J].Advanced Energy Materials,2017,7(3):1601885;
[0146] 7.Ge,B.,Wang,Y.,Sun,Y.,et al.A proof-of-concept of Na-N2 rechargeablebattery[J].Energy Storage Materials,2019,23:733-740;
[0147] 8.Guo,C.,Han,B.,Sun,W.,et al.Hydrogen-Bonded Organic Framework forHigh-Performance Lithium / Sodium-Iodine Organic Batteries[J].AngewandteChemie,2022,134(48):e202213276;
[0148] 9.He,
[0149] 10. Lei, Y., Wu, C., Lu,
[0150] 11. Wu, S., Qiao, Y., Jiang, K., et al. Tailoring sodium anodes for stable sodium-oxygen batteries [J]. Advanced Functional Materials, 2018, 28(13): 1706374;
[0151] 12.Sun, B., Kretschmer, K., Xie,
[0152] like Figure 3 The distribution of discharge products and ion transport mechanism were analyzed using secondary time-of-flight ion mass spectrometry ( Figure 3 (a) to (e)) demonstrate that the bicontinuous structure (bicontinuous carbon) has obvious advantages in ion transport compared with NC carbon materials without bicontinuous structure. During a discharge process, sodium chloride can be evenly distributed in the bicontinuous structure ( Figure 3 (a), (c)), demonstrating that sodium ions can diffuse rapidly in the bicontinuous structure, while carbon materials without bicontinuous structures show obvious sodium chloride aggregation ( Figure 3(b), (d)). We further used particle stacking simulation to analyze the diffusion of sodium chloride in different carbon structures ( Figure 3 (f)~(h)), which further proves the experimental results in time-of-flight secondary ion mass spectrometry, that is, ions can diffuse uniformly and effectively in the carbon cathode with a bicontinuous structure.
[0153] like Figure 4 As shown, the capture of chlorine by the cathode material and the kinetics of the NaCl / Cl2 conversion reaction were analyzed. The nitrogen doping in the bicontinuous structure (bicontinuous carbon) has a certain binding effect on chlorine, thereby limiting the crosstalk of this oxidizing gas to the negative electrode and the electrolyte. X-ray photoelectron spectroscopy proves the interaction between N and chlorine, that is, the formation of N-Cl bonds ( Figure 4 (a)). We also used density functional theory to calculate the interaction between N and chlorine, proving that the conjugated structure (C=NC=C) of pyrrole N and pyridine N sites can disperse the negative charge on the N atom, thereby reducing the dipole-induced effect ( Figure 4 (b)), while chlorine can be distributed horizontally on graphite N sites ( Figure 4 (c)), this is because the interaction induced by ion-dipole force and dispersion force is stronger than the vertical adsorption configuration induced by dispersion force. And graphite N also shows the lowest adsorption energy for chlorine, proving that graphite N has a strong interaction with chlorine ( Figure 4 (d)). The nitrogen element also plays a role in the kinetics of the NaCl / Cl2 conversion reaction. We calculated the free energy changes of the NaCl / Cl2 conversion reaction at different nitrogen-doped sites and proved that pyrrolic nitrogen can achieve the lowest reaction energy barrier ( Figure 4 (f)). The above results demonstrate that N-doping in bicontinuous carbon can effectively achieve Cl2 adsorption and fast NaCl / Cl2 conversion reaction kinetics.
[0154] like Figure 5 As shown, we use schematic diagrams to further describe the advantages of the bicontinuous structure (bicontinuous carbon) in Na / Cl2 batteries, namely, fast ion transport can achieve uniform product distribution in the positive electrode material, thereby realizing an excellent solid-liquid-gas three-phase interface, while the doping of N element realizes the adsorption of gaseous Cl2 and obtains fast NaCl / Cl2 conversion reaction kinetics.
[0155] In order to more conveniently illustrate the outstanding advantages of the present invention, the carbon materials recorded in other documents are applied to chlorine batteries and the corresponding performances are summarized in the following table for comparison:
[0156]
[0157] 13. Zhu, G., Liang, P., Huang, CL, et al. High-capacity rechargeable Li / Cl2batteries with graphite positive electrodes[J]. Journal of the American Chemical Society, 2022, 144(49): 22505-22513.
[0158] 14.Xu,Y.,Jiao,L.,Ma,J.,et al.Metal-organic frameworks fornanoconfinement of chlorine in rechargeable lithium-chlorine batteries[J].Joule,2023,7(3):515-528.
[0159] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a bicontinuous structure nitrogen-doped carbon material based on a co-assembly method, characterized in that The main steps include: (1) 10 to 30 mg of polystyrene-b-polyethylene oxide and 10 to 30 μL of pyrrole are completely mixed and dissolved in an organic solvent to prepare a precursor solution; The organic solvent is 1,4-dioxane solvent, or a mixture of 1,4-dioxane and N,N-dimethylformamide in a volume ratio of (76-88):(12-24) as the organic solvent; (2) adding 1.5 to 2.5 mL of a poor solvent to the precursor solution obtained in step (1) at a rate of 0.5 to 2 mL / h, stirring during the addition, and continuing to stir for 1 to 3 hours after the addition is completed; then adding a polymerization initiator to carry out a polymerization reaction, and washing and drying the polymerization reaction product as an intermediate product; (3) calcining the intermediate product obtained in step (2) to obtain a bicontinuous structure nitrogen-doped carbon material; wherein the calcination treatment is specifically as follows: heating the intermediate product obtained in step (2) to 350-400°C under an inert gas atmosphere, retaining the heat treatment at this temperature for 2-3 hours, then heating it to 750-850°C, continuing the heat treatment at this temperature for 2-3 hours, and obtaining a bicontinuous structure nitrogen-doped carbon material after cooling.
2. The method according to claim 1, characterized in that: The poor solvent in step (2) is deionized water.
3. The method according to claim 2, characterized in that: In step (2), 1.5 to 2.5 mL of deionized water is added dropwise at a rate of 0.8 to 1 mL / h.
4. The method according to claim 1, characterized in that: The step (2) of adding a polymerization initiator to carry out a polymerization reaction is specifically as follows: adding 0.5 to 2 mL of an aqueous solution of ammonium persulfate and carrying out a polymerization reaction for 7 to 9 hours with stirring.
5. The method according to claim 1 or 4, characterized in that: During the polymerization reaction in step (2), the pH value is adjusted to 9-11 to reduce the polymerization reaction rate.
6. The method according to claim 1, characterized in that: The calcination treatment in step (3) has a heating rate of 2 to 3°C / min.
7. A bicontinuous structure nitrogen-doped carbon material prepared by the method for preparing a bicontinuous structure nitrogen-doped carbon material based on a co-assembly method according to claim 1.
8. Use of the bicontinuous structure nitrogen-doped carbon material according to claim 7 as a battery material.
9. Use of the bicontinuous structure nitrogen-doped carbon material according to claim 7 in the preparation of the positive electrode of a sodium / chlorine battery.
Citation Information
Patent Citations
Nitrogen-oxygen co-doped bicontinuous nano-porous carbon material as well as preparation method and application thereof
CN112537771A
Mesoporous carbon nitride material and process for producing the same
WO2008126799A1